2004
DOI: 10.1128/iai.72.12.7202-7211.2004
|View full text |Cite
|
Sign up to set email alerts
|

Toll-Like Receptor 9 Can Be Expressed at the Cell Surface of Distinct Populations of Tonsils and Human Peripheral Blood Mononuclear Cells

Abstract: Unmethlylated CpG dinucleotides induce a strong T-helper-1-like inflammatory response, presumably mediated by Toll-like receptor 9 (TLR9). However, the nature and cellular localization of TLR9 in primary human cells remain controversial. Here we demonstrate, using flow cytometry and immunofluorescence microscopy techniques, that TLR9 can be expressed at the cell surface. The primary human cell subsets that were positive for TLR9 expression were distinct depending on the tissues analyzed. Specifically, in human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(73 citation statements)
references
References 35 publications
3
68
2
Order By: Relevance
“…Hemmi et al [86] demonstrated that TLR-9 is required for the immune activation by CpG-dinucleotides. This receptor is highly expressed on plasmacytoid precursor DC, B cells, and cells of the monocytes/MØ lineage [53,104,239]. Whereas a lot of studies demonstrated an intracellular presence, more recent studies also show cell surface expression.…”
Section: Tlr9-bindingmentioning
confidence: 98%
See 1 more Smart Citation
“…Hemmi et al [86] demonstrated that TLR-9 is required for the immune activation by CpG-dinucleotides. This receptor is highly expressed on plasmacytoid precursor DC, B cells, and cells of the monocytes/MØ lineage [53,104,239]. Whereas a lot of studies demonstrated an intracellular presence, more recent studies also show cell surface expression.…”
Section: Tlr9-bindingmentioning
confidence: 98%
“…Whereas a lot of studies demonstrated an intracellular presence, more recent studies also show cell surface expression. Upon IFNγ treatment, both TLR9 mRNA expression and responsiveness to CpG DNA are upregulated in PBMC, whereas LPS upregulates cell surface expression [53].…”
Section: Tlr9-bindingmentioning
confidence: 99%
“…It is now appreciated that TLR9 can engage a wide range of microbial infections including bacteria (42,43), viral (44,45), and parasitic (8,9,15). TLR9 has been localized to several tissues and cell types, including the gastric mucosa, tonsils (29,46), IECs, Paneth cells in the gut mucosa, B cells, and several DC populations (2,15,39,(47)(48)(49).…”
Section: Discussionmentioning
confidence: 99%
“…These cells could be stained with both murine CpG DNA and human CpG DNA. CpG DNA may bind to TLR9 as well as other binding proteins, thereby staining intracellular and plasma membrane compartments (23)(24)(25). Hence, these immunostimulatory DNA molecules stain appropriate cells, suggesting that differential responses are not due to cell association.…”
Section: Cpg Dna Staining Of Cellsmentioning
confidence: 99%